Key Factors Affecting Egyptian SMEs Performance with the Mediating Role of E-Commerce Adoption - Elziaty, Sameh Mohamed Talaat; Saad, Mohamed; Magdi, Dalia Ahmed; Ragab, Aiman Ahmed (The Arab Journal of Administration, 2024)
The main goal of this paper is to enhance understanding of the factors that affect the adoption of e-commerce in small and medium-sized enterprises (SMEs) in Egypt, and how this affects their performance. The study seeks to analyze the role of e-commerce adoption as a mediator, considering technological, organizational, and environmental factors, on SME performance. The research methodology is quantitative, utilizing a cross-sectional survey approach. Data was gathered through an online questionnaire from Egyptian SME owner-managers, chief executive officers, or managers and analyzed using regression analysis and ANOVA in the SPSS program. Results indicate that technological, organizational, and environmental factors have a positive and significant impact on e-commerce adoption, which in turn positively and significantly affects SME performance. The study also found that e-commerce adoption mediates the relationship between technological and environmental factors with SME performance, but it does not in the organizational factors case. These findings hold significant implications for the Egyptian government, IT vendors, and SME owners, as they can use the results to create effective programs that encourage e-commerce adoption in Egyptian SMEs. Overall, this study contributes to both theory and practice by providing a realistic view of e-commerce adoption, the key factors that lead to adoption, and their effect on SME performance.